SYNTHESIS, CHARACTERIZATION OF ANTIMICROBIAL ACTIVITY OF 22’ DICHLOROHYDROBENZOIN - B, Thanuja; Kanagam, Charles (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this work to evaluate the antimicrobial activities of synthesized 22'dichlorohydrobenzoin (22'CD) a new organic crystal. Methods: 22'CD a new organic crystal was grown by vapor diffusion method. Single crystals of 22'CD have been subjected to X-ray diffraction analysis to estimate the lattice parameters and the space group. The molecular structure was confirmed using Fourier transform infrared and nuclear magnetic resonance (NMR) spectral analyses. Optical behavior and thermal stability of the crystal were determined using UV-Vis spectroscopy and thermogravimetry-differential thermal analysis curves. In the present study, antimicrobial activity of 22'CD was evaluated against Escherichia coli and Bacillus subtilis was evaluated by agar well diffusion method. Results: Antibacterial activity of 22'CD was analyzed with ciprofloxacin and miconazole standard and tested against E. coli, Pseudomonas aeruginosa, Salmonella paratyphi, Klebsiella pneumonia's, Staphylococcus aureus, Streptococcus progenies, and B. subtilis. Conclusion: The 22'CD was found to be effective against E. coli and B. subtitles.